History of the boundary dispute between Ecuador and Peru (1921)
The purpose of this treatise is to describe and explain to English-speaking readers the essentials of what is possibly the most complicated boundary question in Hispanic-America today. In composing the work the basic idea has been, not to insert a series of translations of documents accompanied by a slender thread of exposition-which would have meant mainly a compilation-but to indicate, in a form that while brief will be clear of comprehension, the nature, origin and development of the matter. Although in the concluding chapters an effort is made to estimate the issues involved, the primary object remains that of a historical, rather than that of a legal and diplomatic, presentation of the subject.